The Influence of Spiritual Leadership, Organizational Culture on Employee Engagement, and Organizational Commitment, Organizational Culture as a Mediation - Agus Siswanto (Proceedings of Femfest International Conference on Economics, Management, and Business, 2024)
This study aims to develop a conception of the direct influence of spiritual leadership and organizational culture on employee engagement with organizational commitment as an intervening variable in Islamic microfinance institutions. This study uses the Partial Least Square-Structural Equation Modeling (PLS-SEM) approach as a data analysis technique. Partial Least Square (PLS) is an alternative data analysis technique from Structural Equation Modeling (SEM). The objects in this study were 174 employees from KSPPS BMT UGT Nusantara which is the largest sharia microfinance institution in Indonesia. The result of this research is that there is no direct positive and significant effect of spiritual leadership on employee engagement. There is no direct positive and significant effect between organizational culture on employee engagement. There is a positive and significant direct effect between organizational commitment on employee engagement. There is a direct positive and significant influence between spiritual leadership on organizational commitment. There is a direct positive and significant influence between organizational culture on organizational commitment. There is a direct positive and significant influence between spiritual leadership on organizational culture. There is an indirect positive and significant influence between spiritual leadership on employee engagement through organizational commitment mediation. There is an indirect positive and significant influence between organizational culture on employee engagement through organizational commitment mediation. There is no positive and significant indirect effect between spiritual leadership on employee engagement through organizational culture partial mediation.